Cross-Border Currency Exposures - Benetrix, Agustin; Gautam, Deepali; Juvenal, Luciana; Schmitz, Martin (Washington, D.C. : International Monetary Fund, 2019)
This paper provides a dataset on the currency composition of the international investment position for a group of 50 countries for the period 1990-2017. It improves available data based on estimates by incorporating actual data reported by statistical authorities and refining estimation methods. The paper illustrates current and new uses of these data, with particular focus on the evolution of currency exposures of cross-border positions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet